Management of acute lower gastrointestinal bleeding by pharmaco-induced vasospasm embolization therapy. Issue 2 (7th February 2022) - Li, Ming-Feng; Liang, Huei-Lung; Chiang, Chia-Ling; Lin, Yih-Huie
Abstract : Background: To report the clinical outcomes of vasospasm embolization technique in treating lower gastrointestinal bleeding (LGIB). Methods: Fifty LGIB patients (32 men and 18 women; mean age, 70.4 years) with positive contrast extravasation on multidetector computed tomography were treated with pharmaco-induced vasospasm embolization by semiselective catheterization technique. Distal rectal bleeding was excluded. The bleedings in three patients were considered to be tumor related. Eighteen underwent regular hemodialysis, and 22 showed unstable hemodynamic at intervention. Results: Forty-two bleeders were found in superior mesenteric territory and eight in the inferior mesenteric territory. Successful, immediate hemostasis was achieved in 49 (98%) patients. Early recurrent bleeding (<30 days) was found in 13 (26.5%) patients with 6 local rebleeding (12.2%), 5 new-foci bleeding (10.2%), and 2 uncertain foci bleeding (4.1%). Repeated vasospasm embolization therapy was given to five patients, with successful hemostasis in four. All the three tumor-related bleeding patients undergoing vasospasm embolization had ceased bleeding and discharged. Patient-based primary and overall clinical successes were achieved in 73.5% and 83.7%, and lesion-based primary and overall clinical successes were 83.0% and 86.7%, respectively. The 30-day mortality rate was 21.3%, and the 1- and 2-year survival rates were 51.5% and 43.8%. No major procedure-related complications (eg, bowel ischemia) were encountered. Conclusion: This study confirmed our prior preliminary conclusion that pharmaco-induced vasospasm embolization is easy, safe, and effective for LGIB. This treatment may be considered the first-line alternative approach for LGIB, especially for patients of advanced age with complex medical problems and/or when vasa rectal embolization isn't feasible.